Strategi Manajemen Perubahan Usaha Salon Dan Spa di Era Distruptif (Studi Nurayya Salon & Spa Muslimah) - Maliyah, Ningtias Aprili; Aslami, Nuri (Universitas Labuhanbatu, 2022)
Lately, many Muslim salon businesses have sprung up in areas where the Muslim community is densely packed. Nurayya Salon & Spa Muslimah, Nurayya is a service company. In early 2013, when it was first established, Nurayya used the name Narayya, located in the center of Surabaya. The type of research used in this study is a qualitative descriptive method. In the face of changes in this disruptive era, Nurayya tends to face internal changes by prioritizing its vision of becoming the best Muslim salon & spa in Indonesia. Then when the covid hit and people were increasingly afraid to go out of the house, Nurayya used the Home Treatment so that all customers could feel safe & comfortable without having to leave the house.